GC-MS analysis, antibacterial, antioxidant study and brine shrimp lethality analysis of Trachyspermum ammi (L.) Sprague - D.C., Shova; Maharjan, Binita; Shrestha, Timila; Bharati, Samjhana; Shrestha, Ram Lal (Amrit Research Journal, 2020)
Fruit part of Trachyspermum ammi (L.) Sprague was subjected to extraction of essential oil by hydrodistillation in Clevenger apparatus. So collected essential oil was analyzed by GC-MS for its composition and exhibited the presence of 10 different compounds. The most abundant were γ-terpinene (53.81%) and thymol (29.40%). Antibacterial activity was performed against six bacterial species and Staphylococcus aureus, Enterobacter cloaceae and Bacillus subtilis were the most susceptible to the essential oil showing zone of inhibition (ZOI) 1.4, 1.5 and 1.4 cm respectively. The IC50 value of the oil against DPPH was found to be 0.94 mg/mL. The LC50 value of essential oil of T. ammi against brine shrimp was found 26.2 μg/mL.